A method for preparing a water-based lubricant-stainless steel sealer
Patent Information
- Application Number
- CN202611167574.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
AI Technical Summary
这些问题的根源在于,现有技术多依赖市售原料的简单物理复配,各组分独立发挥作用,未通过分子层面的结构设计和工艺时序配合来构建协同的成膜体系
1.本申请将硝酸铈与羟基亚乙基二膦酸预先在弱酸性条件下进行络合反应,得到含有机磷酸铈络合物的反应混合液,该反应混合液在液相中保持可溶性,避免了铈离子直接以无机盐形式加入水基配方时易水解生成沉淀的问题。同时,嵌段聚醚脂肪酸酯反应混合物中的环氧乙烷链段亲水、环氧丙烷链段亲油,在封闭剂水相中形成胶束结构,提高了各组分相容性,使产品长期存放不易分层。
Smart Images

Figure CN122979031A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sealing agent technology, specifically relating to a method for preparing a water-based lubricant-stainless steel sealing agent. Background Technology
[0002] Stainless steel sealant is a surface treatment material coated on the surface of stainless steel to fill the micropores of the passivation film and block corrosive media. Water-based lubricants for stainless steel sealant also provide lubrication. They are commonly used for short-term protection after cold working processes such as stamping and stretching of stainless steel sheets, and can also be used for inter-process rust prevention of precision parts. These products use water as the main dispersion medium and contain organic film-forming substances, corrosion inhibitors, and lubricants. During application, a thin and uniform protective film is formed on the metal surface through dip coating or spraying, reducing the coefficient of friction and delaying corrosion.
[0003] Currently, commonly used water-based sealing agents in industry are mostly based on simple blends of organophosphates or organophosphate esters and organic amines, supplemented by long-chain fatty acid salts or polyoxyethylene ether nonionic surfactants as lubricating and dispersing components. Organophosphates rely on their phosphonic acid groups to form coordination bonds with iron and chromium oxides on stainless steel surfaces, providing a chemical anchoring effect; organic amines are used to adjust pH and promote film formation; and polyoxyethylene ether components provide interfacial lubrication. Some formulations also introduce silicates or small amounts of soluble cerium salts to improve the corrosion resistance of the film.
[0004] The aforementioned conventional formulations have long suffered from several unavoidable problems in actual production. First, organophosphates and organic amines typically coexist in a physical mixture, failing to form an ordered supramolecular structure. This results in disordered molecular arrangement during film formation, insufficient film density, and a tendency for early rust spots to appear during salt spray testing. Second, organophosphates exhibit poor selectivity in binding to active sites on metal surfaces, leaving numerous micropores and defects in the film, limiting its ability to block corrosive media such as chloride ions. Third, the significant differences in the hydrophilic-lipophilic balance among the components lead to stratification and flocculation during long-term storage, requiring re-stirring before use and affecting application stability. Fourth, the lack of chemical cross-linking between components after film formation results in low film cohesion, poor abrasion resistance and water resistance, and easy damage from slight friction. Fifth, the lubricating components exist only as physical fillers in the film, failing to form entanglement or anchorage with the film-forming skeleton. Under friction conditions, they are prone to precipitation and migration from the film, leading to insufficient lubrication durability.
[0005] To address the issue of insufficient membrane density, some studies have attempted to add rare earth salts, such as cerium nitrate, to the formulation, utilizing the hydrolysis of cerium ions to generate oxides that fill membrane defects. However, this approach typically involves adding cerium salts directly to the water-based formulation as inorganic salts. Cerium ions readily hydrolyze in weakly alkaline or neutral aqueous phases to form cerium hydroxide precipitate, leading to turbidity and gelation during the formulation stage, making it impossible to obtain a uniform and stable blocking agent product. Regarding component stratification, some formulations improve the situation by increasing the amount of emulsifier or increasing the stirring speed. However, this only provides temporary physical stability; phase separation will still occur after prolonged storage, and excessive emulsifier can reduce the water resistance of the membrane. To address the issue of low crosslinking density after film formation, some researchers have introduced silane coupling agents. However, conventional silanes exhibit excessively rapid self-condensation rates in the aqueous phase, often forming silica gel particles during the formulation stage, making uniform dispersion impossible and hindering their crosslinking effect in the later stages of film formation.
[0006] In summary, existing water-based lubricants-stainless steel sealants exhibit interconnected shortcomings in film density, liquid phase stability, post-film crosslinking density, and lubrication durability. The root cause of these problems lies in the fact that current technologies largely rely on simple physical compounding of commercially available raw materials, with each component acting independently, without employing molecular-level structural design and process timing coordination to construct a synergistic film-forming system. Therefore, a method for preparing water-based lubricants-stainless steel sealants needs to be designed. Summary of the Invention
[0007] To overcome the shortcomings of the prior art, a method for preparing a water-based lubricant-stainless steel sealant is provided.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a water-based lubricant-stainless steel sealant, the method comprising the following steps: a. 0.5-2 parts by mass of cerium nitrate and organic phosphoric acid are complexed under weakly acidic conditions at a molar ratio of 1:2-1:4 to obtain a reaction mixture containing cerium organophosphate complex. The mixture is then directly added to 20-30 parts by mass of deionized water and stirred at 30-40℃ for 15-20 min to obtain a pre-complexed solution. b. Partially neutralize 8-15 parts by weight of long-chain alkyl alcohol phosphate with polyether amine in an ether alcohol solvent to obtain a phosphate ester polyether amine salt reaction mixture; partially esterify 3-6 parts by weight of block polyether with long-chain fatty acid in the presence of a catalyst to obtain a block polyether fatty acid ester reaction mixture; hydrolyze 2-4 parts by weight of polymethyl methoxysiloxane with ether alcohol and water under acidic conditions to obtain a methoxysiloxane ether alcohol reaction mixture; mix the above three reaction mixtures, add 5-10 parts by weight of ether alcohol solvent, stir at 50-60℃ for 30-40 min, cool to below 40℃ to obtain a modified film-forming phase; c. Dissolve 3-7 parts by weight of long-chain fatty acid polyoxyethylene ester in 15-25 parts by weight of deionized water, heat to 45-55℃ and stir to dissolve to obtain a lubricating phase; d. Add the modified film phase obtained in step b to the pre-complexed solution in step a, and stir at 35-45℃ for 20-30 min; e. Add the lubricating phase obtained in step c to the mixture in step d, add deionized water, so that the total content of deionized water in the sealing agent is 55-72 parts by mass, and stir at 25-35℃ for 40-60 min; f. Add 2-5 parts by weight of triethanolamine, adjust the pH to 5.8-6.5, stir at 20-30℃ for 10-15 minutes, and filter to obtain a clear and transparent sealing agent product.
[0009] In step b, the ether alcohol solvent is propylene glycol methyl ether.
[0010] In step c, the long-chain fatty acid polyoxyethylene ester is stearate polyoxyethylene ester.
[0011] In step a, the organic phosphoric acid is hydroxyethylidene diphosphonic acid, the weakly acidic conditions are pH 3.5-5.0, the reaction temperature is 40-60℃, and the reaction time is 1-2h.
[0012] In step b, the long-chain alkyl alcohol phosphate ester and polyetheramine undergo a partial neutralization reaction in an ether alcohol solvent. The amount of ether alcohol solvent used is 0.8-1.2 times the mass of the phosphate ester. The reaction is carried out at 60-80°C with stirring for 1-3 hours. The degree of neutralization is 30%-70% by controlling the amount of polyetheramine added.
[0013] The long-chain alkyl alcohol phosphate is monolaurate phosphate; the number average molecular weight of the polyetheramine is 400-2000, and its EO to PO molar ratio is 3:1-1:1; the ether alcohol solvent is ethylene glycol monobutyl ether.
[0014] In step b, the block polyether and long-chain fatty acid are reacted at a hydroxyl to carboxyl molar ratio of 1:0.4-1:0.6 in the presence of p-toluenesulfonic acid, with the catalyst amount being 0.5%-1.0% of the total mass of the reactants. The reaction is carried out at 140-160℃ for 3-5 hours, during which time samples are taken regularly to determine the acid value. When the esterification rate reaches 40%-60%, heating is stopped and the temperature is lowered to below 80℃. Sodium carbonate powder is added to neutralize the residual acid, and the solids are removed by filtration.
[0015] The block polyether is an EO-PO block polyether with a number average molecular weight of 1000-3000 and hydroxyl groups at the end, and the EO to PO molar ratio is 1:1-2:1; the long-chain fatty acid is lauric acid or stearic acid.
[0016] In step b, the block polyether and long-chain fatty acid are reacted at a hydroxyl to carboxyl molar ratio of 1:0.4-1:0.6. In the presence of the catalyst p-toluenesulfonic acid and a dehydrating agent, the amount of catalyst is 0.5%-1.0% of the total mass of the reactants. The reaction is carried out under reflux at 140-160℃ for 3-5 hours. During the reaction, the generated water is continuously separated by a water separator. When the esterification rate reaches 40%-60%, heating is stopped, the dehydrating agent is removed by vacuum distillation, the temperature is lowered to below 80℃, sodium carbonate powder is added to neutralize the residual acid, and the solids are removed by filtration.
[0017] The polymethylmethoxysiloxane has a number average molecular weight of 500-1500, and its terminal silicon atoms have an average of 2-3 methoxy groups; the ether alcohol is ethylene glycol monobutyl ether or propylene glycol methyl ether.
[0018] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. This application involves pre-complexing cerium nitrate and hydroxyethylidene diphosphonic acid under weakly acidic conditions to obtain a reaction mixture containing an organophosphate cerium complex. This reaction mixture remains soluble in the liquid phase, avoiding the problem of easy hydrolysis and precipitation when cerium ions are directly added to an aqueous formulation as inorganic salts. Simultaneously, the ethylene oxide segments in the block polyether fatty acid ester reaction mixture are hydrophilic, while the propylene oxide segments are lipophilic, forming a micelle structure in the aqueous phase of the blocking agent. This improves the compatibility of the components and prevents the product from easily separating during long-term storage.
[0019] 2. This application achieves chemical anchoring by controlling the amount of polyetheramine added to neutralize the phosphate ester polyetheramine salt reaction mixture. The free acid groups retained in the product can form coordination bonds with iron or chromium oxides on the stainless steel surface. After coating, as moisture evaporates, cerium ions in the organophosphate cerium complex undergo controlled hydrolysis and condensation to generate a cerium-oxygen-phosphorus network, which embeds into the gaps between the film layers to fill micropore defects. The phosphonic acid groups of excess organophosphate also form bidentate coordination with the metal surface, further enhancing adhesion.
[0020] 3. This application retains hydrolyzable methoxy groups in the methoxysiloxane ether alcohol reaction mixture. During the later stages of film formation, the methoxy groups undergo hydrolysis and condensation under ambient humidity and slightly alkaline conditions to form a siloxane-silicon crosslinking network. This network, together with the cerium-oxygen-phosphorus network and the phosphorus-oxygen-iron and phosphorus-oxygen-chromium coordination networks, constitutes a three-dimensional composite network, locking each component within the film layer, improving the film layer's cohesion, and making the film layer less prone to swelling and detachment when exposed to water or wiped.
[0021] 4. This application uses polyoxyethylene stearate as the lubricating phase. Its polyoxyethylene chains form molecular entanglements with the polyetheramine chains in the phosphate ester polyetheramine salt reaction mixture and the ethylene oxide chains in the block polyether fatty acid ester reaction mixture, preventing the lubricating components from precipitating from the film. Under frictional conditions, polyoxyethylene stearate migrates to the interface, reducing the coefficient of friction. Furthermore, due to the molecular entanglement, the lubricating components are less prone to loss, thus improving lubrication durability. Attached Figure Description
[0022] Figure 1 This is a process flow diagram of the preparation method of a water-based lubricant-stainless steel sealant according to the present invention. Detailed Implementation
[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] In the specific embodiments of this application, the sources of various main raw materials are briefly described as follows: Cerium nitrate: purchased from Shandong Desheng New Materials Co., Ltd., CAS No. 10294-41-4, hexahydrate; Hydroxyethylidene diphosphonic acid: purchased from Wuhan Jiyesheng Chemical Co., Ltd., CAS No. 2809-21-4; Monolaurate phosphate: purchased from Guangzhou Huayu Fine Chemical Co., Ltd., CAS No. 12751-23-4; Polyetheramine: purchased from Changzhou Shanfeng Chemical Co., Ltd., CAS No. 9046-10-0, number average molecular weight 400-2000; Ethylene glycol monobutyl ether: purchased from Shandong Xinheng Chemical Co., Ltd., CAS No. 111-76-2; Oxalic acid: purchased from Shandong Xinheng Chemical Co., Ltd., CAS No. 144-62-7; Block polyether: purchased from Haian Petrochemical Plant in Jiangsu Province, the chemical composition is polyoxyethylene-polyoxypropylene block polymer, the number average molecular weight is 1000-3000; Polyoxyethylene stearate: purchased from Haian Petrochemical Plant, Jiangsu Province, CAS No. 9004-99-3; Lauric acid: purchased from Shanghai Shengyue International Trade Co., Ltd., CAS number 143-07-7; Stearic acid: purchased from Shanghai Shengyue International Trade Co., Ltd., CAS No. 57-11-4; p-Toluenesulfonic acid: purchased from Shandong Yukang Chemical Co., Ltd., CAS No. 104-15-4; Sodium carbonate: purchased from Shandong Haihua Group Co., Ltd., CAS No. 497-19-8; Propylene glycol methyl ether: purchased from Nantong Runfeng Petrochemical Co., Ltd., CAS No. 107-98-2; Triethanolamine: Purchased from Jinan Chuangshi Chemical Co., Ltd., CAS No. 102-71-6; Polymethyl methoxysiloxane: purchased from Shandong Binruit New Material Co., Ltd., CAS 68037-85-4, number average molecular weight 1000.
[0025] The technical solution of this application is as follows: A method for preparing a water-based lubricant-stainless steel sealant, such as... Figure 1 As shown, the method includes the following steps: a. 0.5-2 parts by mass of cerium nitrate and organic phosphoric acid are complexed under weakly acidic conditions at a molar ratio of 1:2-1:4 to obtain a reaction mixture containing cerium organophosphate complex. The mixture is then directly added to 20-30 parts by mass of deionized water and stirred at 30-40℃ for 15-20 min to obtain a pre-complexed solution. Existing water-based lubricants and stainless steel sealants typically add organic phosphoric acid and cerium salts directly to the formulation. Cerium ions are easily hydrolyzed and precipitated in the aqueous phase, leading to product turbidity or even gelation, making it impossible to coat evenly and resulting in numerous film defects.
[0026] In step a of this application, cerium nitrate and hydroxyethylidene diphosphonic acid are pre-treated under weakly acidic conditions to obtain a reaction mixture containing a cerium organophosphate complex. The phosphonic acid groups in the organophosphate molecules form a stable, soluble complex with cerium ions. This complex remains dispersed in the liquid phase and does not undergo significant hydrolysis during storage. After coating, as moisture evaporates, the concentrations of cerium ions and organophosphate increase sharply, the dielectric constant of the system decreases, and the polarity decreases significantly, shifting the complexation-dissociation equilibrium of the complex towards hydrolysis-condensation. Cerium ions undergo controlled hydrolysis in the coordination environment of the organophosphate, generating a cerium-oxygen-phosphorus network structure that embeds itself in the interlayer of the film, filling micropore defects. Because organophosphate is present in excess during the reaction, its uncomplexed phosphonic acid groups can form bidentate coordination bonds with iron or chromium oxides on the stainless steel surface, namely phosphorus-oxygen-iron bonds and phosphorus-oxygen-chromium bonds, enhancing the adhesion between the film and the substrate.
[0027] b. Partially neutralize 8-15 parts by weight of long-chain alkyl alcohol phosphate with polyether amine in an ether alcohol solvent to obtain a phosphate ester polyether amine salt reaction mixture; partially esterify 3-6 parts by weight of block polyether with long-chain fatty acid in the presence of a catalyst to obtain a block polyether fatty acid ester reaction mixture; hydrolyze 2-4 parts by weight of polymethyl methoxysiloxane with ether alcohol and water under acidic conditions to obtain a methoxysiloxane ether alcohol reaction mixture; mix the above three reaction mixtures, add 5-10 parts by weight of ether alcohol solvent, stir at 50-60℃ for 30-40 min, cool to below 40℃ to obtain a modified film-forming phase; However, simply filling defects is insufficient to solve the problem of the disordered arrangement of the film-forming framework itself. In existing technologies, long-chain alkyl alcohol phosphates and organic amines often coexist in a simple physical mixing manner, lacking ionic bonding between molecules, resulting in a disordered arrangement and low cohesive strength during film formation. In step b of this application, monolauryl phosphate and polyetheramine undergo a partial neutralization reaction in ethylene glycol monobutyl ether to obtain a phosphate ester polyetheramine salt reaction mixture. By controlling the amount of polyetheramine added, the degree of neutralization is maintained within a certain range, and the product simultaneously retains free acid groups and unprotonated amine groups. The free acid groups can form chemical coordination bonds with the oxides on the stainless steel surface, achieving anchoring. The ethylene oxide and propylene oxide segments in the polyetheramine chain provide steric hindrance and water solubility, enabling the film-forming framework to be stably dispersed in the aqueous phase. The unneutralized amine groups form intermolecular hydrogen bonds with adjacent free phosphate groups in the later stage of film formation, constructing a primary hydrogen bond network and improving the cohesive strength of the film layer.
[0028] The hydrophilic-lipophilic balance of the various reaction products and auxiliary components mentioned above varies considerably, and stratification easily occurs after long-term storage following simple mixing. In step b of this application, EO-PO block polyether is partially esterified with lauric acid or stearic acid in the presence of p-toluenesulfonic acid to obtain a block polyether fatty acid ester reaction mixture. By controlling the esterification rate, the product retains free hydroxyl and ester groups. The ethylene oxide segments in the molecule are hydrophilic, and the propylene oxide segments are lipophilic, forming a micelle structure in the aqueous phase of the blocking agent, improving the compatibility of the components and preventing stratification during long-term storage. After coating on a stainless steel surface, with the evaporation of moisture and the increase of temperature, the propylene oxide segments undergo reverse dissolution, precipitating from the aqueous phase and directionally adsorbing onto the metal interface, improving wettability and spreadability. Free hydroxyl groups can form hydrogen bonds and coordination bonds with the phosphonic acid groups of organophosphates and metal surface oxides, further anchoring the film layer.
[0029] Existing technologies lack chemical cross-linking between components after film formation, resulting in low cross-linking density and poor water and abrasion resistance. In step b of this application, polymethyl methoxysiloxane is hydrolyzed with ethylene glycol monobutyl ether or propylene glycol methyl ether and deionized water in the presence of oxalic acid to obtain a methoxysiloxane ether alcohol reaction mixture. The product retains hydrolyzable methoxy groups. During the later stages of film formation, these methoxy groups undergo hydrolysis and condensation under humid conditions and trace amounts of alkalinity, forming a siloxane-silicon cross-linked network. This network, together with the cerium-oxygen-phosphorus network, phosphorus-oxygen-iron network, and phosphorus-oxygen-chromium coordination network, constitutes a three-dimensional composite network, locking the components within the film layer and improving film density, water resistance, and abrasion resistance.
[0030] c. Dissolve 3-7 parts by weight of long-chain fatty acid polyoxyethylene ester in 15-25 parts by weight of deionized water, heat to 45-55℃ and stir to dissolve to obtain a lubricating phase; In existing technologies, lubricating components are mostly dispersed in the film layer through physical filling, which easily precipitates out of the film layer during friction, resulting in insufficient lubrication durability. In step c of this application, polyoxyethylene stearate is dissolved in deionized water to obtain a lubricating phase. Its polyoxyethylene chains form molecular entanglements with the polyetheramine chains of phosphate ester polyetheramine salt and the ethylene oxide chains of block polyether, preventing the lubricating components from precipitating out of the film layer. Under friction conditions, polyoxyethylene stearate migrates to the interface, reducing the coefficient of friction and improving lubrication durability.
[0031] d. Add the modified film phase obtained in step b to the pre-complexed solution in step a, and stir at 35-45℃ for 20-30 min; e. Add the lubricating phase obtained in step c to the mixture in step d, add deionized water, so that the total content of deionized water in the sealing agent is 55-72 parts by mass, and stir at 25-35℃ for 40-60 min; f. Add 2-5 parts by weight of triethanolamine, adjust the pH to 5.8-6.5, stir at 20-30℃ for 10-15 minutes, and filter to obtain a clear and transparent sealing agent product.
[0032] The timing of each step is crucial for the liquid-phase stability of the sealing agent and the subsequent film quality. Step d involves adding the modified film-forming phase to the pre-complexed solution to ensure uniform dispersion of the components. Step e involves adding the lubricating phase and replenishing with deionized water to adjust the total deionized water content in the sealing agent. Step f is the final addition of triethanolamine to adjust the pH to a near-neutral to slightly acidic range, resulting in a clear and transparent sealing agent product. This timing ensures that the reaction mixture containing the organophosphate cerium complex remains acidically stable during liquid-phase preparation and storage, preventing premature hydrolysis due to premature contact with triethanolamine. The modified film-forming phase is added after cooling to avoid local instability caused by temperature shock. The final addition of triethanolamine ensures the liquid-phase stability of the sealing agent product during storage. After the sealing agent product is coated onto the stainless steel surface, as moisture evaporates, the local environment slowly changes, causing the organophosphate cerium complex to undergo hydrolysis and condensation, and the methoxy groups in the methoxysiloxane ether alcohol reaction mixture to undergo hydrolysis and condensation. Each crosslinking reaction proceeds in an orderly manner, forming a structurally complete and performance-balanced composite film layer on the metal surface.
[0033] In step b, the ether alcohol solvent is propylene glycol methyl ether.
[0034] In step c, the long-chain fatty acid polyoxyethylene ester is stearate polyoxyethylene ester.
[0035] In step a, the organic phosphoric acid is hydroxyethylidene diphosphonic acid, the weakly acidic conditions are pH 3.5-5.0, the reaction temperature is 40-60℃, and the reaction time is 1-2h.
[0036] In step b, the long-chain alkyl alcohol phosphate ester and polyetheramine undergo a partial neutralization reaction in an ether alcohol solvent. The amount of ether alcohol solvent used is 0.8-1.2 times the mass of the phosphate ester. The reaction is carried out at 60-80°C with stirring for 1-3 hours. The degree of neutralization is 30%-70% by controlling the amount of polyetheramine added.
[0037] The long-chain alkyl alcohol phosphate is monolaurate phosphate; the number average molecular weight of the polyetheramine is 400-2000, and its EO to PO molar ratio is 3:1-1:1; the ether alcohol solvent is ethylene glycol monobutyl ether.
[0038] In step b, the block polyether and long-chain fatty acid are reacted at a hydroxyl to carboxyl molar ratio of 1:0.4-1:0.6. In the presence of the catalyst p-toluenesulfonic acid and a dehydrating agent, the amount of catalyst is 0.5%-1.0% of the total mass of the reactants. The reaction is carried out under reflux at 140-160℃ for 3-5 hours. During the reaction, the generated water is continuously separated by a water separator. When the esterification rate reaches 40%-60%, heating is stopped, the dehydrating agent is removed by vacuum distillation, the temperature is lowered to below 80℃, sodium carbonate powder is added to neutralize the residual acid, and the solids are removed by filtration.
[0039] The block polyether is an EO-PO block polyether with a number average molecular weight of 1000-3000 and hydroxyl groups at the end, and the EO to PO molar ratio is 1:1-2:1; the long-chain fatty acid is lauric acid or stearic acid.
[0040] In step b, the polymethylmethoxysiloxane is reacted with ether alcohol and deionized water in a molar ratio of 1:1-1.5:0.6-1.2. In the presence of oxalic acid as a catalyst, the amount of catalyst is 0.3%-0.8% of the total mass of the reactants. The pH is adjusted to 4.0-5.0, and the mixture is stirred at 50-70°C until the solution changes from turbid to clear.
[0041] The polymethylmethoxysiloxane has a number average molecular weight of 500-1500, and its terminal silicon atoms have an average of 2-3 methoxy groups; the ether alcohol is ethylene glycol monobutyl ether or propylene glycol methyl ether.
[0042] The present invention will be described in detail below through examples and comparative examples, but the scope of protection of the present invention is not limited to these examples. Unless otherwise specified, the chemical reagents and raw materials used in the following examples and comparative examples are all conventional commercially available products.
[0043] Example 1 Two parts by mass of cerium nitrate (hexahydrate) and hydroxyethylidene diphosphonic acid were complexed at a molar ratio of 1:2 at pH 4.0 and a temperature of 50°C for 1.5 h to obtain a reaction mixture containing cerium organophosphate complex. The mixture was then directly added to 25 parts by mass of deionized water and stirred at 30°C for 20 min to obtain a pre-complexed solution.
[0044] 11.5 parts by mass of monolauryl phosphate was partially neutralized with polyetheramine in ethylene glycol monobutyl ether (EDGME), with the amount of EEGME being 1.0 times the mass of phosphate. The reaction was carried out at 70°C with stirring for 2 hours. The degree of neutralization was controlled to 30% by controlling the amount of EEGME added, resulting in a phosphate ester polyetheramine salt reaction mixture. 3 parts by mass of block polyether was reacted with lauric acid at a hydroxyl to carboxyl molar ratio of 1:0.4 in the presence of p-toluenesulfonic acid. The catalyst amount was 0.75% of the total mass of the reactants. 10 parts by mass of toluene was added as a dehydrating agent. The reaction was refluxed at 150°C for 4 hours. During the reaction, a water separator was used to continuously separate the generated water to promote the esterification reaction. Acid values were measured periodically. When the esterification rate reached 60%, heating was stopped, and toluene was removed by vacuum distillation. The mixture was cooled to below 80°C, and sodium carbonate powder was added to neutralize the residual acid. The solids were removed by filtration, resulting in a block polyether fatty acid ester reaction mixture.
[0045] Four parts by mass of polymethyl methoxysiloxane were mixed with ethylene glycol monobutyl ether and deionized water in a molar ratio of 1:1.5:1.2. In the presence of oxalic acid as a catalyst (0.55% of the total mass of reactants), the pH was adjusted to 4.5, and the mixture was stirred at 60°C until the solution changed from turbid to clear, yielding a methoxysiloxane ether alcohol reaction mixture. The above three reaction mixtures were then mixed, and 7.5 parts by mass of propylene glycol methyl ether were added. The mixture was stirred at 55°C for 35 minutes and cooled to below 40°C to obtain the modified film-forming phase.
[0046] Dissolve 3 parts by weight of polyoxyethylene stearate in 20 parts by weight of deionized water, heat to 50°C and stir to dissolve, obtaining a lubricating phase. Add the modified film-forming phase to the pre-complexed solution and stir at 40°C for 25 min. Add the lubricating phase to the mixture, add deionized water to make the total deionized water content in the sealing agent 72 parts by weight, and stir at 30°C for 50 min. Add 3.5 parts by weight of triethanolamine, adjust the pH to 6.2, stir at 25°C for 12 min, and filter to obtain a clear and transparent sealing agent product.
[0047] Example 2 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: 0.5 parts by mass of cerium nitrate and hydroxyethylidene diphosphonic acid were complexed at a molar ratio of 1:4 at pH 3.5 and a temperature of 40°C for 2 hours to obtain a reaction mixture containing organophosphate cerium complex. This mixture was then directly added to 30 parts by mass of deionized water and stirred at 40°C for 15 minutes to obtain a pre-complexed solution.
[0048] Partial neutralization of 15 parts by mass of monolauryl phosphate with polyetheramine in ethylene glycol monobutyl ether (EDE) was carried out. The amount of EED is 1.2 times the mass of phosphate. The reaction was stirred at 80°C for 1 hour. The degree of neutralization was controlled to 70% by controlling the amount of polyetheramine added, resulting in a phosphate ester polyetheramine salt reaction mixture. 4.5 parts by mass of block polyether and stearic acid were reacted at a hydroxyl to carboxyl molar ratio of 1:0.6 in the presence of p-toluenesulfonic acid. The catalyst amount was 1.0% of the total mass of the reactants. 10 parts by mass of toluene was added as a dehydrating agent. The reaction was refluxed at 140°C for 3 hours. During the reaction, water was continuously separated using a water separator to promote the esterification reaction. Acid value was measured periodically. When the esterification rate reached 40%, heating was stopped and the temperature was lowered to below 80°C. Sodium carbonate powder was added to neutralize the residual acid. The solids were removed by filtration, resulting in a block polyether fatty acid ester reaction mixture. Two parts by mass of polymethyl methoxysiloxane were mixed with ethylene glycol monobutyl ether and deionized water in a molar ratio of 1:1.0:0.6. In the presence of oxalic acid as a catalyst (0.3% of the total mass of reactants), the pH was adjusted to 4.0, and the mixture was stirred at 50°C until the solution changed from turbid to clear, yielding a methoxysiloxane ether alcohol reaction mixture. The above three reaction mixtures were then mixed, and 10 parts by mass of propylene glycol methyl ether were added. The mixture was stirred at 60°C for 30 minutes and cooled to below 40°C to obtain the modified film-forming phase.
[0049] Five parts by weight of polyoxyethylene stearate were dissolved in 25 parts by weight of deionized water, and the solution was heated to 55°C and stirred until dissolved to obtain a lubricating phase. The modified film-forming phase was added to the pre-complexed solution and stirred at 45°C for 20 min. The lubricating phase was added to the mixture, and deionized water was added to make the total deionized water content in the sealing agent 55 parts by weight. The solution was stirred at 35°C for 40 min. Five parts by weight of triethanolamine were added to adjust the pH to 5.8, and the solution was stirred at 30°C for 10 min. The mixture was then filtered to obtain a clear and transparent sealing agent product.
[0050] Example 3 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: 1.25 parts by mass of cerium nitrate and hydroxyethylidene diphosphonic acid were complexed at a molar ratio of 1:3 at pH 4.5 and a temperature of 50°C for 1.5 h to obtain a reaction mixture containing organophosphate cerium complex. This mixture was then directly added to 22 parts by mass of deionized water and stirred at 35°C for 18 min to obtain a pre-complexed solution.
[0051] Partial neutralization of 8 parts by mass of monolauryl phosphate with polyetheramine in ethylene glycol monobutyl ether (0.9 times the mass of phosphate) was carried out at 65°C with stirring for 2.5 h. The degree of neutralization was controlled to 50% by controlling the amount of polyetheramine added, resulting in a phosphate ester polyetheramine salt reaction mixture. 6 parts by mass of block polyether and lauric acid were reacted at a hydroxyl to carboxyl molar ratio of 1:0.5 in the presence of p-toluenesulfonic acid, with a catalyst amount of 0.6% of the total mass of reactants. 10 parts by mass of toluene were added as a dehydrating agent, and the mixture was refluxed at 155°C for 4.5 h. During the reaction, a water separator was used to continuously separate the generated water to promote the esterification reaction. Acid values were measured periodically. When the esterification rate reached 50%, heating was stopped and the temperature was lowered to below 80°C. Sodium carbonate powder was added to neutralize the residual acid, and the solids were removed by filtration, yielding a block polyether fatty acid ester reaction mixture. Three parts by mass of polymethyl methoxysiloxane were mixed with ethylene glycol monobutyl ether and deionized water in a molar ratio of 1:1.2:0.8. In the presence of oxalic acid as a catalyst (0.6% of the total mass of reactants), the pH was adjusted to 4.8, and the mixture was stirred at 65°C until the solution changed from turbid to clear, yielding a methoxysiloxane ether alcohol reaction mixture. The above three reaction mixtures were then mixed, and five parts by mass of propylene glycol methyl ether were added. The mixture was stirred at 50°C for 40 min, and then cooled to below 40°C to obtain the modified film-forming phase.
[0052] Seven parts by weight of polyoxyethylene stearate were dissolved in 18 parts by weight of deionized water, and the solution was heated to 48°C and stirred until dissolved to obtain a lubricating phase. The modified film-forming phase was added to the pre-complexed solution and stirred at 38°C for 30 min. The lubricating phase was added to the mixture, and deionized water was added to make the total deionized water content in the sealing agent 63.5 parts by weight. The mixture was stirred at 28°C for 55 min. Two parts by weight of triethanolamine were added to adjust the pH to 6.0, and the mixture was stirred at 22°C for 14 min. The mixture was then filtered to obtain a clear and transparent sealing agent product.
[0053] Example 4 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: 1.5 parts by mass of cerium nitrate and hydroxyethylidene diphosphonic acid were complexed at a molar ratio of 1:3 at pH 4.0 and a temperature of 50°C for 1.5 h to obtain a reaction mixture containing organophosphate cerium complex. This mixture was then directly added to 25 parts by mass of deionized water and stirred at 35°C for 18 min to obtain a pre-complexed solution.
[0054] Partial neutralization of 12 parts by mass of monolauryl phosphate with polyetheramine in ethylene glycol monobutyl ether (EDE) was carried out. The amount of EED is 1.0 times the mass of phosphate. The reaction was stirred at 70°C for 2 hours. The degree of neutralization was controlled to 50% by controlling the amount of polyetheramine added, resulting in a phosphate ester polyetheramine salt reaction mixture. 4 parts by mass of block polyether and lauric acid were reacted at a hydroxyl to carboxyl molar ratio of 1:0.5 in the presence of p-toluenesulfonic acid. The catalyst amount was 0.75% of the total mass of the reactants. 10 parts by mass of toluene were added as a dehydrating agent. The reaction was refluxed at 150°C for 4 hours. During the reaction, water was continuously separated using a water separator to promote the esterification reaction. The acid value was measured periodically. When the esterification rate reached 50%, heating was stopped and the temperature was lowered to below 80°C. Sodium carbonate powder was added to neutralize the residual acid. The solids were removed by filtration, resulting in a block polyether fatty acid ester reaction mixture. Three parts by mass of polymethyl methoxysiloxane were mixed with ethylene glycol monobutyl ether and deionized water in a molar ratio of 1:1.2:0.8. In the presence of oxalic acid as a catalyst (0.5% of the total mass of reactants), the pH was adjusted to 4.5, and the mixture was stirred at 60°C until the solution changed from turbid to clear, yielding a methoxysiloxane ether alcohol reaction mixture. The above three reaction mixtures were then mixed, and eight parts by mass of propylene glycol methyl ether were added. The mixture was stirred at 55°C for 35 minutes and cooled to below 40°C to obtain the modified film-forming phase.
[0055] Five parts by weight of polyoxyethylene stearate were dissolved in 20 parts by weight of deionized water, and the solution was heated to 50°C and stirred until dissolved to obtain a lubricating phase. The modified film-forming phase was added to the pre-complexed solution and stirred at 40°C for 25 min. The lubricating phase was added to the mixture, and deionized water was added to make the total deionized water content in the sealing agent 65 parts by weight. The solution was stirred at 30°C for 50 min. Three parts by weight of triethanolamine were added to adjust the pH to 6.2, and the solution was stirred at 25°C for 12 min. The mixture was then filtered to obtain a clear and transparent sealing agent product.
[0056] Comparative Example 1 This comparative example is basically the same as Example 1, except that in step a, 2 parts by mass of cerium nitrate are directly added to 25 parts by mass of deionized water without prior complexation reaction with hydroxyethylidene diphosphonic acid. The remaining steps are the same as in Example 1.
[0057] Comparative Example 2 This comparative example is basically the same as Example 2, except that in step b, 15 parts by mass of monolauryl phosphate and polyetheramine are completely neutralized in ethylene glycol monobutyl ether, and the amount of polyetheramine is controlled to make the degree of neutralization 100%. The remaining steps are the same as in Example 2.
[0058] Comparative Example 3 This comparative example is basically the same as Example 3, except that in step b, 6 parts by mass of block polyether reacts with lauric acid in the presence of p-toluenesulfonic acid until the esterification rate is 100%, and the remaining steps are the same as in Example 3.
[0059] Comparative Example 4 This comparative example is basically the same as Example 4, except that the preparation and addition of the methoxysiloxane ether alcohol reaction mixture are omitted in step b. The remaining steps are the same as in Example 4.
[0060] Comparative Example 5 This comparative example is basically the same as Example 1, except that in step b, 4 parts by mass of polymethyl methoxysiloxane are reacted with ethylene glycol monobutyl ether and deionized water in a molar ratio of 1:2:4 to completely hydrolyze the methoxy group. The remaining steps are the same as in Example 1.
[0061] Performance Test Results and Analysis The sealing agent products prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were subjected to the following tests. The appearance and static stability of the products were observed. Each sample was left to stand at room temperature for 30 days, and the occurrence of stratification, precipitation, or flocculation was recorded. Stainless steel test plates were pretreated by degreasing, pickling, and passivation, and then each sealing agent sample was dipped into the plate. The plates were dried at 80°C for 20 minutes to form a uniform film. A neutral salt spray test was conducted according to GB / T 10125, and the time when the first rust point appeared on the test plate surface was recorded. The coefficient of friction of the film was tested using a reciprocating friction tester with a load of 5 N, a frequency of 2 Hz, a GCr15 steel ball as the grinding material, and a test stroke of 10 mm. The stable coefficient of friction was recorded. The coated test plates were immersed in deionized water at 25°C for 24 hours. After removal, the changes in the appearance of the film were observed, and the cross-cut adhesion was tested according to GB / T 9286. Use absorbent cotton soaked in anhydrous ethanol to wipe the coating surface 50 times, observe the damage to the film layer, and test the salt spray time of the test panel after wiping. Specific test results are shown in Table 1.
[0062] Table 1 Analysis of Test Results Example 1 Clarity and transparency, no stratification within 30 days 68 0.12 0 No change 45 Example 2 Clarity and transparency, no stratification within 30 days 74 0.11 0 No change 52 Example 3 Clarity and transparency, no stratification within 30 days 70 0.12 0 No change 48 Example 4 Clarity and transparency, no stratification within 30 days 96 0.08 0 No change 72 Comparative Example 1 The mixture was cloudy during preparation, with sediment at the bottom. 18 0.18 2 membrane blistering 8 Comparative Example 2 Clarity and transparency, no stratification within 30 days 42 0.15 1 The film is white 28 Comparative Example 3 Clarify and make transparent; stratify after 3 days. 36 0.14 2 membrane peeling 18 Comparative Example 4 Clarity and transparency, no stratification within 30 days 58 0.13 1 membrane swelling 32 Comparative Example 5 Clarity and transparency, no stratification within 30 days 52 0.13 1 membrane softening 26 As shown in Table 1, Examples 1 to 4 remained clear and transparent after standing at room temperature for 30 days, without stratification or precipitation. Liquid phase stability and storage performance directly reflect the suitability of the sealing agent during transportation and storage. The appearance stability results in Table 1 indicate that cerium nitrate pre-formed a soluble complex with hydroxyethylidene diphosphonic acid under weakly acidic conditions, preventing the direct hydrolysis of cerium ions in the aqueous phase to form hydroxide precipitates. Simultaneously, the ethylene oxide and propylene oxide segments in the block polyether fatty acid ester reaction mixture formed a micelle structure in the aqueous phase, improving the compatibility of the components and allowing hydrophobic components such as the phosphate ester polyether amine salt reaction mixture and the methoxysiloxane ether alcohol reaction mixture to be stably dispersed. Comparative Example 1 showed turbidity and precipitation during the preparation stage because cerium nitrate was not pre-complexed, and cerium ions directly hydrolyzed in the aqueous phase, disrupting the homogeneity of the liquid phase. Comparative Example 3 showed stratification after standing for 3 days. This is because after the block polyether reacted with lauric acid to 100% esterification, there were no free hydroxyl residues in the product. The original amphiphilic structure of the block polyether was completely destroyed, and it could not form a stable micelle structure in the aqueous phase, resulting in decreased compatibility of the components and deterioration of liquid phase stability.
[0063] The density and corrosion resistance of the film are core functional indicators of the sealant. Salt spray test results reflect the film's ability to block corrosive media such as chloride ions. Example 4 achieved a salt spray time of 96 hours, while Examples 1 to 3 ranged from 68 to 74 hours. In Example 4, all parameters were in optimal balance. After film formation, the concentrations of cerium ions and organic phosphoric acid in the organophosphate cerium complex increased sharply with water evaporation, significantly reducing the system's polarity. This shifted the complexation-dissociation equilibrium of the complex towards hydrolysis-condensation, and the resulting cerium-oxygen-phosphorus network effectively filled the microporous defects in the film. Simultaneously, the free acid groups retained in the phosphate ester polyetheramine salt reaction mixture formed chemical coordination bonds with iron or chromium oxides on the stainless steel surface, providing a strong chemical anchor and ensuring a tight bond between the film and the substrate, reducing the channels for corrosive media to penetrate along the interface.
[0064] In Comparative Example 1, the salt spray time was only 18 hours. Precipitation in the liquid phase directly led to dense defects in the film layer, preventing the formation of a continuous and dense protective film. Comparative Example 2 had a salt spray time of 42 hours. Although the liquid phase was stable, the phosphate ester polyether amine salt reaction mixture had a 100% neutralization degree, with no residual free acid groups. This weakened the chemical anchoring effect with the metal surface, resulting in insufficient bonding strength between the film layer and the substrate, allowing corrosive media to easily penetrate along the interface. Comparative Example 3 had a salt spray time of 36 hours. Complete esterification not only destroyed the amphiphilicity of the block polyether fatty acid ester reaction mixture, leading to liquid phase stratification, but the absence of free hydroxyl groups after film formation also significantly weakened the interfacial anchoring effect, resulting in poor adhesion between the film layer and the metal surface and further deterioration of salt spray performance. Comparative Example 4 had a salt spray time of 58 hours. Although it possessed chemical anchoring and defect-filling functions, the omission of the methoxysiloxane ether alcohol reaction mixture resulted in the absence of a silica-silicon crosslinking network in the later stages of film formation. This led to insufficient cohesion in the film layer, with numerous microscopic permeable channels allowing corrosive media to penetrate. The salt spray time of Comparative Example 5 was 52 hours. After the methoxy groups were completely hydrolyzed, there were no hydrolyzable methoxy groups in the product. Therefore, an effective three-dimensional cross-linked network could not be formed in the later stage of film formation. The film density was between that of Comparative Example 4 and the Example, but it was still far from reaching the level of the Example.
[0065] Interfacial lubrication and friction properties reflect the friction-reducing ability of the sealant during cold working or assembly of stainless steel. Table 1 shows that the coefficient of friction for Example 4 is 0.08, while that for Examples 1 to 3 ranges from 0.11 to 0.12. This may be because the polyoxyethylene chains of stearic acid polyoxyethylene ester form molecular entanglements with the polyetheramine chains in the phosphate ester polyetheramine salt reaction mixture and the ethylene oxide chains in the block polyether fatty acid ester reaction mixture, locking the lubricating components within the film and preventing their precipitation during storage. During friction, stearic acid polyoxyethylene ester migrates to the interface to form lubricating microdomains, reducing the coefficient of friction.
[0066] In contrast, the friction coefficient of Comparative Example 1 was 0.18. Precipitation in the liquid phase led to an uneven film layer, which prevented the lubricating components from being effectively dispersed, resulting in high interface roughness during friction. The friction coefficients of Comparative Examples 2 to 5 ranged from 0.13 to 0.15, all higher than those of the examples. This is because complete neutralization in Comparative Example 2 resulted in a loose film structure, making it easy for the lubricating components to be squeezed out; liquid phase stratification in Comparative Example 3 led to an uneven film layer and an irregular distribution of the lubricating phase; the absence of a cross-linked network in Comparative Example 4 resulted in a large amount of lubricating components precipitating out in the early stages of friction, leading to insufficient lubrication in the later stages; and complete hydrolysis of methoxy groups in Comparative Example 5 resulted in insufficient cohesion in the film layer, making it easy for the lubricating components to be lost from the film layer during friction.
[0067] Water resistance and interfacial bonding strength reflect the reliability of the membrane in humid environments. In Examples 1 to 4, the membranes showed no change after 24 hours of immersion, and the cross-cut adhesion was grade 0 in all cases. This is because the free acid groups in the phosphate ester polyether amine salt reaction mixture formed coordination bonds with the metal surface, and the free hydroxyl groups in the block polyether fatty acid ester reaction mixture also formed hydrogen bonds and coordination bonds with the metal surface, providing multiple interfacial anchorings. Simultaneously, the siloxane-silicon cross-linked network formed in the methoxysiloxane ether alcohol reaction mixture during the later stages of film formation locked the components, increasing the membrane cohesion and making it difficult for water molecules to penetrate to the interface or the interior of the membrane.
[0068] Comparative Example 1 showed an adhesion level of 2, with membrane blistering. This was due to the dense defects caused by cerium precipitation, allowing water molecules to penetrate along the defects to the interface and form bubbles. Comparative Example 2 showed an adhesion level of 1, with the membrane turning white. This was because the absence of free acid groups resulted in insufficient chemical anchoring between the membrane and the substrate, allowing water molecules to penetrate along the interface and causing blistering and whitening. Comparative Example 3 showed an adhesion level of 2, with membrane detachment. This was because the complete esterification resulted in the absence of free hydroxyl groups, and the block polyether fatty acid ester reaction mixture lost its interfacial anchoring ability. Water molecules directly disrupted the bond between the membrane and the substrate, leading to large-area membrane detachment. Comparative Example 4 showed an adhesion level of 1, with membrane swelling. This was due to the absence of a silica-oxygen-silicon crosslinking network, resulting in low cohesion and allowing water molecules to penetrate into the membrane, causing swelling. Comparative Example 5 showed an adhesion level of 1, with membrane softening. This was because the complete hydrolysis of methoxy groups left behind a large number of silanol groups or hydrophilic fragments in the product, allowing water molecules to easily penetrate into the membrane and causing softening.
[0069] Abrasion resistance and film durability reflect the remaining protective ability of the sealant after mechanical abrasion. The salt spray time after wiping in Example 4 was 72 hours, while in Examples 1 to 3 it ranged from 45 to 52 hours. In Example 4, the methoxysiloxane ether alcohol reaction mixture retained hydrolyzable methoxy groups. The silica-silicon crosslinking network formed in the later stages of film formation, together with the cerium-oxygen-phosphorus network, phosphorus-oxygen-iron, and phosphorus-oxygen-chromium coordination networks, constituted a three-dimensional composite network, firmly locking the lubricating components and the film skeleton, thus improving the cohesive strength and structural integrity of the film. In Comparative Example 1, the salt spray time after wiping was only 8 hours, and the film was almost completely wiped away. In Comparative Example 2, it was 28 hours; the lack of free acid groups resulted in weak bonding between the film and the substrate, leading to large-area film detachment after wiping. In Comparative Example 3, it was 18 hours; poor interfacial anchoring and liquid phase stratification resulted in an uneven film, exposing defects after wiping, allowing the corrosive medium to directly erode the substrate. Comparative Example 4, after 32 hours, although it exhibited chemical anchoring, it lacked a cross-linking network. After wiping and damaging the film structure, the remaining film layer could not effectively block corrosive media. Comparative Example 5, after 26 hours, showed that after complete hydrolysis of the methoxy groups, it could not form effective cross-links in the later stages of film formation, resulting in insufficient film cohesion and severe damage to the film structure after wiping.
[0070] A side-by-side comparison between Comparative Examples 4 and 5 illustrates the importance of timing control of the siloxane components. Comparative Example 4 completely omitted the methoxysiloxane ether alcohol reaction mixture, resulting in a membrane without siloxane components. Its salt spray time was 58 hours, and after wiping, it was 32 hours. Although Comparative Example 5 introduced siloxanes, the methoxy groups were completely hydrolyzed, resulting in a salt spray time of 52 hours and after wiping, 26 hours, slightly lower than Comparative Example 4. After complete hydrolysis of the methoxy groups, a large number of silanol groups or hydrophilic fragments remained in the product. This not only prevented the formation of an effective three-dimensional cross-linked network but also increased the hydrophilicity of the membrane, accelerating water molecule penetration. This demonstrates that the value of the methoxysiloxane ether alcohol reaction mixture lies not only in introducing silicon but also in retaining hydrolyzable methoxy groups by controlling the degree of hydrolysis, allowing them to undergo timely hydrolysis and condensation in the later stages of film formation to form a complete cross-linked structure. Premature or excessive hydrolysis will disrupt this timing coordination, leading to performance degradation.
[0071] Test results show that this application uses a phosphate ester polyether amine salt reaction mixture, an organophosphate cerium complex reaction mixture, a block polyether fatty acid ester reaction mixture, and a methoxysiloxane ether alcohol reaction mixture to stabilize the liquid phase of the sealing agent and form an in-situ hybrid crosslinked composite film after coating, thus taking into account both liquid phase stability and film density, water resistance, abrasion resistance, and lubrication durability.
[0072] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a water-based lubricant-stainless steel sealant, characterized in that, The method includes the following steps: a. 0.5-2 parts by mass of cerium nitrate and organic phosphoric acid are complexed under weakly acidic conditions at a molar ratio of 1:2-1:4 to obtain a reaction mixture containing cerium organophosphate complex. The mixture is then directly added to 20-30 parts by mass of deionized water and stirred at 30-40℃ for 15-20 min to obtain a pre-complexed solution. b. Partially neutralize 8-15 parts by weight of long-chain alkyl alcohol phosphate with polyether amine in an ether alcohol solvent to obtain a phosphate ester polyether amine salt reaction mixture; partially esterify 3-6 parts by weight of block polyether with long-chain fatty acid in the presence of a catalyst to obtain a block polyether fatty acid ester reaction mixture; hydrolyze 2-4 parts by weight of polymethyl methoxysiloxane with ether alcohol and water under acidic conditions to obtain a methoxysiloxane ether alcohol reaction mixture; mix the above three reaction mixtures, add 5-10 parts by weight of ether alcohol solvent, stir at 50-60℃ for 30-40 min, cool to below 40℃ to obtain a modified film-forming phase; c. Dissolve 3-7 parts by weight of long-chain fatty acid polyoxyethylene ester in 15-25 parts by weight of deionized water, heat to 45-55℃ and stir to dissolve to obtain a lubricating phase; d. Add the modified film phase obtained in step b to the pre-complexed solution in step a, and stir at 35-45℃ for 20-30 min; e. Add the lubricating phase obtained in step c to the mixture in step d, add deionized water, so that the total content of deionized water in the sealing agent is 55-72 parts by mass, and stir at 25-35℃ for 40-60 min; f. Add 2-5 parts by weight of triethanolamine, adjust the pH to 5.8-6.5, stir at 20-30℃ for 10-15 minutes, and filter to obtain a clear and transparent sealing agent product.
2. The preparation method of a water-based lubricant-stainless steel sealant according to claim 1, characterized in that, In step b, the ether alcohol solvent is propylene glycol methyl ether.
3. The preparation method of a water-based lubricant-stainless steel sealant according to claim 1, characterized in that, In step c, the long-chain fatty acid polyoxyethylene ester is stearate polyoxyethylene ester.
4. The preparation method of a water-based lubricant-stainless steel sealant according to claim 1, characterized in that, In step a, the organic phosphoric acid is hydroxyethylidene diphosphonic acid, the weakly acidic conditions are pH 3.5-5.0, the reaction temperature is 40-60℃, and the reaction time is 1-2h.
5. The preparation method of a water-based lubricant-stainless steel sealant according to claim 1, characterized in that, In step b, the long-chain alkyl alcohol phosphate ester and polyetheramine undergo a partial neutralization reaction in an ether alcohol solvent. The amount of ether alcohol solvent used is 0.8-1.2 times the mass of the phosphate ester. The reaction is carried out at 60-80°C with stirring for 1-3 hours. The degree of neutralization is 30%-70% by controlling the amount of polyetheramine added.
6. The method for preparing a water-based lubricant-stainless steel sealant according to claim 5, characterized in that, The long-chain alkyl alcohol phosphate is monolaurate phosphate; the number average molecular weight of the polyetheramine is 400-2000, and its EO to PO molar ratio is 3:1-1:1; the ether alcohol solvent is ethylene glycol monobutyl ether.
7. The preparation method of a water-based lubricant-stainless steel sealant according to claim 1, characterized in that, In step b, the block polyether and long-chain fatty acid are reacted at a hydroxyl to carboxyl molar ratio of 1:0.4-1:0.
6. In the presence of the catalyst p-toluenesulfonic acid and a dehydrating agent, the amount of catalyst is 0.5%-1.0% of the total mass of the reactants. The reaction is carried out under reflux at 140-160℃ for 3-5 hours. During the reaction, the generated water is continuously separated by a water separator. When the esterification rate reaches 40%-60%, heating is stopped, the dehydrating agent is removed by vacuum distillation, the temperature is lowered to below 80℃, sodium carbonate powder is added to neutralize the residual acid, and the solids are removed by filtration.
8. The method for preparing a water-based lubricant-stainless steel sealant according to claim 7, characterized in that, The block polyether is an EO-PO block polyether with a number average molecular weight of 1000-3000 and hydroxyl groups at the end, and the EO to PO molar ratio is 1:1-2:1; the long-chain fatty acid is lauric acid or stearic acid.
9. The preparation method of a water-based lubricant-stainless steel sealant according to claim 1, characterized in that, In step b, the polymethylmethoxysiloxane is reacted with ether alcohol and deionized water in a molar ratio of 1:1-1.5:0.6-1.
2. In the presence of oxalic acid as a catalyst, the amount of catalyst is 0.3%-0.8% of the total mass of the reactants. The pH is adjusted to 4.0-5.0, and the mixture is stirred at 50-70°C until the solution changes from turbid to clear.
10. The method for preparing a water-based lubricant-stainless steel sealant according to claim 9, characterized in that, The polymethylmethoxysiloxane has a number average molecular weight of 500-1500, and its terminal silicon atoms have an average of 2-3 methoxy groups; the ether alcohol is ethylene glycol monobutyl ether or propylene glycol methyl ether.